Translating the French Revolution into English in A Tale of Two Cities - Nathalie Vanfasse (Cahiers Victoriens et Edouardiens)
This article highlights what Dickens was trying to achieve in A Tale of Two Cities when he invented what Sylvère Monod called an “Anglo-French language” (Monod 429-31) composed of English words but borrowing syntactic forms from the French or translating French set phrases literally into English. It argues that Dickens’s creation of a new form of English sprinkled with Gallicisms was part and parcel of a strategy to translate the French Revolution into English. He used this newspeak to fathom the Revolution’s singularity and render it understandable to English-speaking readers. Dickens’s Anglo-French lingua proves more complex and subtle than it may have seemed at first sight. Far from offering mere wordplay and sensational images, it reveals an interesting interpretation of the French Revolution.